The impact of e-commerce adoption towards Small Medium Enterprise (SME) in Pengkalan Chepa, Kelantan - Fadzil, Abdul Wahab; Hanis Syakira, Za’in; Lai, Wen Li; Ganesan, Sateya Sila (2015)
E-commerce technology offers many benefits to organizations of any size including small to medium- sized enterprises (SMEs). The purpose of this study is to identify the relationship between personal factors, environment factors, financial factors and the impacts of e-commerce technology towards SMEs in PengkalanChepa, Kelantan. This research was undertaken in PengkalanChepa, Kelantan by targeting samples that were entrepreneurs of SMEs, students of Universiti Malaysia Kelantan (Main Campus), school students and residents in area of PengkalanChepa, Kelantan. The result was adopting correlation coefficient and reliability analysis on this study showed significant relationship on listed factors that influence SMEs to adopt e-commerce. This way achieved by circulating questionnaires to test the impacts of e-commerce technology towards SMEs in PengkalanChepa, Kelantan. This study provides a clear image on the changes in the way of doing business that influence by transformation of technologies